Studies of radiation effects in Al2O3-based metal-oxide-semiconductor structures induced by Si heavy ions - Zhang, Jia-Wei; Song, Chen (Journal of applied physics, 2019)
The radiation effects of metal-oxide-semiconductor (MOS) capacitors based on an Al2O3 gate dielectric were studied using 30 MeV Si heavy ions. To give insights into the types of defects induced by Si ion irradiation in the gate oxide, synergistic experiments involving γ-ray irradiation and Si ion irradiation were carried out. The results revealed that the defects in the as-grown Al2O3 layer were found to be hole trapping centers, whereas Si ion induced new defects were electron trapping centers. The experimental and simulation data of current density-voltage (J-V) curves confirmed that the transmission mechanism of leakage current in the Al2O3 layer was mainly dominated by the Frenkel-Poole mechanism. In detail, the variations of leakage current were mainly due to the attributions of the local built-in electric field-assisted current leakage and the conductive path-assisted current leakage and were found to be dependent on the irradiation condition and Al2O3 thickness. Lastly, the decrease of the gate oxide capacitance of MOS capacitors was attributed to the increase of the series resistance and leakage current in MOS capacitors.